When the heat is on: High temperature resistance of buds from European tree species. (28th May 2021) - Bär, Andreas; Schröter, Dennis Marko; Mayr, Stefan
Abstract: The heat resistance of meristematic tissues is crucial for the survival of plants exposed to high temperatures, as experienced during a forest fire. Although the risk and frequency of forest fires are increasing due to climate change, knowledge about the heat susceptibility of buds, which enclose apical meristems and thus enable resprouting and apical growth, is scarce. In this study, the heat resistance of buds in two different phenological stages was experimentally assessed for 10 European tree species. Cellular heat tolerance of buds was analyzed by determining the electrolyte leakage following heat exposure. Further, the heat insulation capability was tested by measuring the time required to reach lethal internal temperatures linked to bud traits. Our results highlighted differences in cellular heat tolerance and insulation capability among the study species. The phenological stage was found to affect both the thermal stability of cells and the buds' insulation. Further, a good relationship between size‐related bud traits and insulation capability was established. Species‐specific data on the heat resistance of buds give a more accurate picture of the fire susceptibility of European tree species and provide useful information for estimating tree post‐fire responses more precisely. Abstract : The protection of meristematic tissues located in buds is crucial for the survival of plants exposed to high temperatures, as during a forest fire. This study demonstrated differences in cellular heat tolerance and insulation capability of buds among ten European tree species and evaluated the effect of the phenological stage on the buds' heat resistance.